Biodegradation of diesel oil in marine environment by a floating water droplet - Asadi, F.; Phan, Chi; Obanijesu, E. (Center for Environmental and Energy Research and Studies, 2017)
© 2017, Islamic Azad University (IAU). Diesel oil is one of the derivatives of crude oil which resistance to biodegradation due to its complex structure and low solubility in water. A novel concept of enhancement of diesel degradation using floating water droplet is proposed and being investigated to address some key challenges encountered in diesel oil spillages in the aqueous area and wetlands. This study aims to increase the floatability of a floating water droplet on oil. A droplet containing a mixed consortium of 60 different hydrocarbon degrading bacteria and sodium dodecyl sulfate as a surfactant was deposited on the diesel oil surface. Contact angle and contact radius were monitored to observe the effect of bacterial activities on the droplet. The behavior of this droplet on diesel oil was different to a previous study with paraffin oil. In particular, the floatability, bacterial growth and biofilm formation demonstrate significant deviation due to the diesel interactions with biological processes. Nevertheless, the results show this method increase microbial activities within the droplet. The result verifies the applicability of the floating water droplet as an environmentally friendly method for diesel oil spillages.